A Pilot Approach Investigating the Potential of Crop Rotation With Sainfoin to Reduce Meloidogyne enterolobii Infection of Maize Under Greenhouse Conditions - Rashidifard, Milad; Ashrafi, Samad; Claassens, Sarina; Thünen, Torsten; Fourie, Hendrika (Frontiers in Plant Science, 2021)
Root-knot nematodes (RKNs) are one of the most important plant-parasitic nematodes of cereal crops in sub-Saharan Africa. This study was designed to evaluate the rotation effects of different genotypes of sainfoin (‘Esparsette’, Perly’, ‘Taja’ and ‘Visnovsky’), soybean (‘DM-5953-RSF’) and alfalfa (“BAR 10’) with maize (‘P-2432-R’), on a Meloidogyne enterolobii population, compared to monoculture maize. The results showed that sainfoin (Perly and Esparsette) and alfalfa had significantly (P ≤ 0.05) lower numbers of M. enterolobii eggs and second stage juveniles (J2) compared to the monoculture maize in the first experiment. However, in the repeat experiment all treatments had significantly (P ≤ 0.05) lower numbers of eggs and J2 compared to monoculture maize. Rotation of sainfoin ‘Esparsette’/maize resulted in the lowest numbers of eggs and J2 (91 and 202, respectively) in the first and repeat experiments. Rotation of sainfoin ‘Esparsette’/maize reduced M. enterolobii population density by 81% and 60% in the first and repeat experiments, respectively, followed by alfalfa (54% and 43%, respectively). Ultimately, substantial variation was evident in terms of the efficacy of different sainfoin genotypes with regards to their effect on nematode reduction when used in rotation with maize.